Implementation of TaRL Approach by Utilizing Canva Media to Improve Students’ Collaboration Skills and Learning Outcomes in Science - Hidayah Zuliana Puspitaningrum; Hasan Subekti; Umi Nur Hasanah (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to improve collaborative skills and student learning outcomes in science subjects by using the teaching at the right level (TaRL) learning approach by utilizing Canva media in the learning process. Method: The research method used was classroom action research involving 32 students of class 8B at Junior High School 3 Madiun. The research stage uses the Kemmis & Mc. Taggar model. The survey was conducted in two cycles. Each cycle consists of two meetings including the stages of planning, implementation of actions, observation and reflection. The data sources used in the study are observations during learning, tests, and learning evaluation results. Results: Showing a positive impact of learning using the TaRL approach by using Canva learning media, especially on collaborative skills and student learning outcomes. The results of observation and evaluation showed an improvement in collaboration skills and learning outcomes after implementing the TaRL approach through Canva's learning media. Novelty: This research has a novelty because the use of the TaRL approach with Canva media will bring out students' creativity so that cohesiveness with the team is established, design learning that allows students to obtain learning concepts, and make it easier for teachers to apply this approach in science learning.